A Multi-aspect Sustainability Assessment of Tourism Development in Berau Regerency, East Kalimantan - Aprylasari, Dede; Yoga Toyibulah; Agung Enggal Nugroho; Siti Azizah (Fast in Social Sciences, 2026)
Tourism development in Berau Regency, East Kalimantan, plays a strategic role in driving post-extractive economic transformation by fostering marine and nature tourism. However, pressure on environmental carrying capacity, inequality in economic benefits, limited infrastructure and technology, and disparities in community social capacity pose serious challenges to the sustainability of regional tourism. This study aims to comprehensively analyze the sustainability level of Berau Regency's tourism development through a Multi-aspect Sustainability Analysis (MSA) approach that encompasses ecological, economic, infrastructure, and technology, and social aspects. The study used a quantitative-descriptive approach with 30 expert respondents selected through purposive sampling, including government officials, academics, tourism practitioners, and community representatives. The analysis was conducted using the Exsimpro tool to calculate the sustainability index, determine sustainability status, identify leverage factors, and simulate future conditions (leveraged condition). The results indicate that, in general, Berau Regency's tourism development falls into the less sustainable to borderline sustainable status category for all aspects studied. Ecological, infrastructure, and technology, and social aspects are at the limits of sustainability, while economic aspects show the greatest potential for improvement and are most responsive to strategic interventions. Key levers include environmental carrying capacity, tourism's economic contribution and growth, transportation accessibility, and human resource capacity and community empowerment. These findings underscore the need for an integrated, adaptive, and priority-based cross-sectoral tourism management strategy to drive the transformation toward competitive, inclusive, and sustainable tourism